Subcellular localization of neuronal nitric oxide synthase in the brain of a teleost; an immunoelectron and confocal microscopical study - Holmqvist, Bo; Ekström, Peter (Brain Research, 1997)
The subcellular localization of neuronal nitric oxide (NO) synthase (NOS)-immunoreactive (NOSir) elements in the brain of the Atlantic salmon was investigated by means of electron microscopy and confocal laser scanning microscopy. NOSir structures are present only in neuronal elements. In neuronal processes, strong NOS immunoreactivity was mainly localized within synaptic vesicles or seen as a dense accumulation associated with the plasma membrane of dendrites and at terminal formations. NOSir precipitate was also associated with microtubuli and mitochondrial outer membranes. The highest accumulation of NOS immunoreactivity was found in dendrites located in close apposition to immunonegative myelinated or unmyelinated neural processes. Several NOSir and unmyelinated immunonegative profiles formed synaptic specializations. Immunonegative neurons in contact with NOSir processes always contained round clear synaptic vesicles. In neuronal somata, strong NOS immunoreactivity was localized in the cristae of some large mitochondria, whereas vacuoles and the endoplasmic reticulum showed a relatively weak staining. Confocal microscopic analysis of NOS immunofluorescence showed a corresponding subcellular localization of NOS in different brain regions, but also indicated the presence of NOS axosomatic terminals. Our data show that specific neurons contain a neuronal NOS-like molecule which to a high degree is stored in vesicles and is accumulated at various sites along the neuronal processes or at specific synaptic terminal formations. Thus, NO may be formed and exert its actions at various sites along the processes of NOS-synthesizing neurons. The present study provides evidence at the ultrastructural level that NO may play a messenger role in neural circuits involved in visual and hypophysiotrophic brain functions.